NDP52 acts as a redox sensor in PINK1/Parkin‐mediated mitophagy. (14th December 2022) - Kataura, Tetsushi; Otten, Elsje G; Rabanal‐Ruiz, Yoana; Adriaenssens, Elias; Urselli, Francesca; Scialo, Filippo; Fan, Lanyu; Smith, Graham R; Dawson, William M; Chen, Xingxiang; Yue, Wyatt W; Bronowska, Agnieszka K; et al.
Abstract: Mitophagy, the elimination of mitochondria via the autophagy‐lysosome pathway, is essential for the maintenance of cellular homeostasis. The best characterised mitophagy pathway is mediated by stabilisation of the protein kinase PINK1 and recruitment of the ubiquitin ligase Parkin to damaged mitochondria. Ubiquitinated mitochondrial surface proteins are recognised by autophagy receptors including NDP52 which initiate the formation of an autophagic vesicle around the mitochondria. Damaged mitochondria also generate reactive oxygen species (ROS) which have been proposed to act as a signal for mitophagy, however the mechanism of ROS sensing is unknown. Here we found that oxidation of NDP52 is essential for the efficient PINK1/Parkin‐dependent mitophagy. We identified redox‐sensitive cysteine residues involved in disulphide bond formation and oligomerisation of NDP52 on damaged mitochondria. Oligomerisation of NDP52 facilitates the recruitment of autophagy machinery for rapid mitochondrial degradation. We propose that redox sensing by NDP52 allows mitophagy to function as a mechanism of oxidative stress response. Synopsis: Damaged mitochondria generate excessive amounts of reactive oxygen species (ROS). Here, the human autophagy receptor NDP52 is found to sense this damage through oligomerisation mediated by specific redox‐sensitive cysteine residues, initiating rapid mitophagy. Human NDP52 is oxidised and forms disulphide‐linked conjugates on damaged mitochondria. Four cysteine residues involved in disulphide bond formation are conserved in primates but are not present in other mammals. Introduction of human NDP52 into mouse cells is sufficient to generate redox sensitivity during mitophagy. Disulphide‐mediated oligomerisation of NDP52 on mitochondria facilitates the recruitment of autophagy initiation machinery and mitophagy. Abstract : Human autophagy receptor NDP52 senses reactive oxygen species to mark damaged mitochondria for removal.